Hubungan universiti dan industri untuk pembangunan sumber manusia : kajian kes di universiti-universiti tempatan di Malaysia - Mohamad Adi, Ismail (Universiti Malaysia Sarawak (UNIMAS), 1998)
The major purpose of this study is to determine the features of collaboration between universities and industries in Malaysia, and the benefits it bears to society in the context of human resource development. The study focuses on the modes of collaboration, major areas of concentration, achievements and problems encountered in this collaborative endeavour. Besides, strengths and weaknesses of the universities in the collaborative process is also studied. Additionally, the preparations made by the universities to produce global graduate in the context of this collaborative effort is also examined. The respondents of the study are personnels from UKM, UTM and UNIMAS who are incharged of the collaborative programs. The interviews conducted, tape recorded and then transcribed. The transcribed findings were sorted into various themes based on the objectives of the study. The finding of this study shows that the universities, industries and government must play an active role to bring about successful collaboration. With the existence of the collaborative effort, industries are able to produce quality products, and Universities are able to tum out graduates who are able to compete in the global market. The study also reveals that universities that have effective management system can easily convince industries to collaborate with them. Based on the findings of this study, if is suggested that the universities should provide in-depth and accurate information to the industries and should put every effort to commercialize their research finding in order to enhance the collaborative effort. All parties should recognizel that universities are centres of excellent ill knowledge. The government should also play and active role to enhance the success of collaboration between university and industry.